Geochemical Fingerprinting by Handheld Laser‐Induced Breakdown Spectroscopy. Issue 4 (27th June 2017) - Harmon, Russell S.; Hark, Richard R.; Throckmorton, Chandra S.; Rankey, Eugene C.; Wise, Michael A.; Somers, Andrew M.; Collins, Leslie M.
Abstract : A broad suite of geological materials was studied a using a handheld laser‐induced breakdown spectroscopy (LIBS) instrument. Because LIBS is simultaneously sensitive to all elements, the full broadband emission spectrum recorded from a single laser shot provides a 'chemical fingerprint' of any material – solid, liquid or gas. The distinguishing chemical characteristics of the samples analysed were identified through principal component analysis (PCA), which demonstrates how this technique for statistical analysis can be used to identify spectral differences between similar sample types based on minor and trace constituents. Partial least squares discriminant analysis (PLSDA) was used to distinguish and classify the materials, with excellent discrimination achieved for all sample types. This study illustrates through four examples (carbonate minerals and rocks, the oxide mineral pair columbite–tantalite, the silicate mineral garnet and native gold) how portable, handheld LIBS analysers can be used for real‐time chemical analysis under simulated field conditions for element or mineral identification, plus such applications as stratigraphic correlation, provenance determination and natural resource exploration. Key Points: Because LIBS is simultaneously sensitive to all elements, the full broadband emission spectrum recorded from a single laser shot provides a "chemical fingerprint" of any material. Handheld LIBS systems offer a new tool for real‐time chemical analysis in the field. Geological applications include element detection, mineral identification, stratigraphic correlation, provenance determination and natural resource exploration.